An experimental and DFT study of a disulfide-linked Schiff base: Synthesis, characterization and crystal structure of bis (3-methoxy-salicylidene-2-aminophenyl) disulfide in its anhydrous and monohydrate forms - Ferraresi Curotto, Verónica (2013)
A detailed structural and spectroscopic study of the disulfide Schiff base obtained from condensation of 2-aminothiophenol and o-vanillin is reported. It includes the analyses of the anhydrous and monohydrate forms of the title compound. Structures of both solids were resolved by X-ray diffraction methods. A comparison between experimental and theoretical results is presented. The conformational space was searched and geometries were optimized both in gas phase and including solvent effects. Vibrational (IR and Raman) and electronic spectra were measured and assigned with the help of computational methods based on the Density Functional Theory. Calculated MEP-derived atomic charges were calculated to predict coordination sites for metal complexes formation.